Optimization of hot-air drying conditions on functional properties of flour from dried South African sweet potato cultivars (Impilo and Bophelo) using the response surface methodology - MOLOTO,Phuti Itumeleng (2021)
Abstract The response surface method (RSM) has an important application in formulation of new products. This study determined the effect of electric hot-air drying on the functional properties of flour made from orange-fleshed sweet potato (OFSP). Flour from the cultivars Bophelo (B) and Impilo (IM) were treated with 13 temperature-time combinations designed by STAT EASE software version 8.01.0. Bophelo flour dried at 70 °C for 8.6 hrs and Impilo at 70 °C for 14.4 hrs showed the lowest gelatinization temperatures and enthalpy of gelatinization (ΔH), indicating ease of cooking. The highest swelling power of 12.45 g/g for Bophelo and 8.16 g/g for Impilo were significantly higher than the remaining samples. Flours for Bophelo and Impilo at drying temperatures and times at 70 °C for 4.4 hrs, 56 °C for 6.5 hrs and 60 °C for 6.5 hrs indicated favourable gelling properties and cost of drying, implying that these can be used at household level and in food industries as thickeners from both cultivars.